Multidimensionality within the Edinburgh postnatal depression scale: application issues of specific structure - Ratislavová, Kateřina; Hendrych Lorenzová, Eva; Lochmannová, Alena; Martin, Colin R (Journal of reproductive and infant psychology, 2025)
OBJECTIVE AND BACKGROUND: The 10-item Edinburgh Postnatal Depression Scale (EPDS) is a widely-used screening measure for postnatal depression. Factor analysis studies have suggested an embedded sub-scale could be used for screening for anxiety disorders. The current investigation sought to replicate and extend a recent study supporting this assertion. METHODS: A cross-sectional design. EPDS data were collected at up to two years postpartum. Confirmatory factor analysis, correlational and distributional characteristics of the measure were examined. Participants were a large sample (N = 985) of postpartum women in the Czech Republic. RESULTS: Factor structure findings substantially replicated the models evaluated by Della Vedova et al. (2022). Bifactor models, however, offered a better fit to data. A general factor of depression explained most of the variance in data in most models compared to embedded sub-scales across models. CONCLUSION: The model proposed by Della Vedova et al. (2022) offered an excellent fit to data. However, the findings from the bifactor modelling suggest the dominance of a general factor of depression which indicates the potential application of an embedded anxiety sub-scale for screening may be overstated.
Keywords: Psychometrics; Young Adult; Cross-Sectional Studies; Depression, Postpartum; psychometrics; factor structure; mladý dospělý; Česká republika; poporodní deprese; Adult; dospělí; Edinburgh Postnatal Depression Scale (EPDS); screening; reprodukovatelnost výsledků; faktorová analýza statistická; Reproducibility of Results; validity; Czech Republic; Factor Analysis, Statistical; lidé; ženské pohlaví; psychometrie; Humans; průřezové studie; psychiatrické posuzovací škály; Female; Psychiatric Status Rating Scales